Criminal, administrative, finance and legal aspects of the use of artificial intelligence in the legal sphere: foreign experience and prospects for Ukraine under martial law - Halunko, Valentyn; Kozlenko, Oleksandr; Kobrusieva, Yevheniiа; Pryimachenko, Dmytro; Ustynova, Iryna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. The article studies the nature of artificial intelligence in foreign countries, in particular in criminal law, financial, administrative regulation. It is substantiated that the use of artificial intelligence in courts will improve the quality of court decisions and increase the efficiency and objectivity of decisions in the authorities. In 2023, a US federal court ruled on the possibility of registering copyright to a work of fine art created by the artificial intelligence DABUS (United States District Court for the District of Columbia [2023]: Thaler v. Perlmutter, № 22-CV-384-1564-BAH). It should be noted that the introduction of legal regulation of artificial intelligence is critical to ensure its safe and ethical use. International cooperation and harmonization of the regulatory framework can contribute to the creation of an effective regulatory system that takes into account the interests of all parties and promotes innovation, while protecting human rights and freedoms. Thus, the analysis of large amounts of data can identify patterns and trends in court decisions and in general in the activities of public administration, and software can influence the forecasting of risks. A number of serious challenges and risks are associated with the purpose of ensuring the security of personal data and the validity of court decisions using artificial intelligence technologies. According to the results of the study, it is proved that artificial intelligence in judicial activity is possible only if effective legal mechanisms are introduced that allow coordinating and regulating these processes.Key words: Administrative regulation, Artificial intelligence, Court decision, Financial regulation, Criminal basis, Assessment, Evidence, Fairness, Reasonableness, Justification.